(untitled) (Palíndromo, 2016)
This article discusses the paths of academic research recognizing them as crossings processes. Through the graphi- cal representation of a work by Hakuin Ekaku - Two blind men crossing a log bridge – parallels are traced between the crossings of research and the crossing of the men illustrated by Hakuin Ekaku: the uncertainties, challenges, solitudes, su- pport and achievements experienced on the path of evolutionary development; the crossings of not- knowing to the knowledge. It presents also the analysis on two master’s theses, a completed one and another in progress, as a way to re- cognize some of these concerns and ex- periences that move being a researcher.